English Teacher and Students' Experiences in Learning Loss at Upper Secondary School During Online Learning in Indonesia - Devi Puspitasari; Evynurul Laily Zen; Yusnita Febrianti (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
Online learning due to the Covid-19 pandemic has been broadly regulated for the past two years in Indonesia. However, there is a limited exploration of the experiences of students and teachers in the English learning loss at upper secondary level students. Thus, this study aimed to fill this gap by exploring the English teacher and students' experiences in learning loss of online English field during the pandemic outbreak. A narrative inquiry was implied to express their voices. Online questionnaire to know students’ demographic background was employed. One English teacher and two third grade students shared their experiences through the narrative interview (NI). The findings showed that English teachers felt students' loss in English subjects rather than the previous cohort. Some students decreased their understanding and motivation in learning English and had to take remedial courses while missing the examination or assignments. Meanwhile, students mentioned they experienced difficulties in learning English through an online classroom. They felt they had degraded their English skills because they did not practice it at home. Moreover, they also lost interest and motivation to join the class and submit the assignments. Those factors initiated the loss in English learning for first-year secondary students.